Gastrografin® (diatrizoate meglumine and diatrizoate sodium solution) induced acute renal failure following lower GI examination and subsequent colonoscopic biopsy. Issue 1 (February 2017) - Patel, D.; Hansmann, J.; Gunasekaran, S.; Goettl, C.; Khan, S.; Sepahdari, A.
Highlights: Gastrografin intravasation after lower GI enema and colonoscopic biopsy. Shortly after the procedure the patient developed acute renal failure. Non-contrast CT demonstrated persistent nephrograms.